THE ENGLISH PROFICIENCY TRAINING IN BANDUNG ORPHANAGES - Meltareza, Ridma; Wiryany, Detya; Aryanti Rasyi Lubis, Ira; Tawaqal, Rizki Surya; Ramdan, Ahmad Taufiq Maulana (Inaba of Community Services Journal, 2022)
Indonesian people are increasingly aware of the importance of English language skills. Not only in communicating academically but also in communication that occurs daily as a result of the increasing flow of information through various media. For people who have access to a place to learn and practice English skills, of course, they will be able to master their skills more effectively. But not with school students who have to study online where not all students have sufficient facilities and access to learn and practice English. For less fortunate students, such as residents of orphanages, mentoring and training activities, both academic and non-academic, they need. So this Community Service activity was carried out. English language training for orphans and poor people was held at the Mutiara Bani Sholihin Orphanage. This activity uses the Quantum teaching method where this method fosters an atmosphere of togetherness, comfort and calmness in learning. Then at the end of this activity session, an evaluation of the material that has been implemented is carried out to measure learning achievement.